Improving Students' Vocabulary Using Jumbled Words At The Fifth Grade Of SD N 03 Mojo Andong Boyolali In 2011/2012 Academic Year - Sabardani, Faizah, Dr. Anam Sutopo, S. Pd, M. Hum, Dra. Dwi Haryanti, M. Hum (2013)
This research aims at describing the improving of students' vocabulary using jumbled words to the fifth grade students of SDN 03 Mojo, Andong, Boyolali. The general objective of this research is to describe the improving students' vocabulary by using jumbled words. While the specific objectives of this research are to know whether or not jumbled words can improve the students' vocabulary, and to identify the strengths and weaknesses of teaching vocabulary using jumbled words to the fifth grade students of SDN 03 Mojo, Andong, Boyolali in 2011/2012 Academic Year. In this research, the writer uses Classroom Action Research (CAR). There are two cycles in this action research in which each cycle is conducted in two meetings. Each cycle of this action research consists of four steps: planning, acting, observing, and reflecting. The research was held in the fifth grade of SDN 03 Mojo, Andong, Boyolali consisting of 20 students. In analyzing the data, the writer uses qualitative analysis from observation, test, interview, and document analysis. The result of research shows that jumbled words can improve students' vocabulary. It can be seen from increasing mean score of pre-test and post-test. The pre-test is 59.1 and post-test is 86.5, the improvement got by the students is 27.4. The strengths are the students can reduce their error possibility, more active, creative, more concentration and are not easily bored in English class. The weaknesses are the writer must spend her spare time at home to prepare material and design the classroom activity, and the writer should use both Indonesia and English language. Thus, it can be said that teaching English vocabulary using Jumbled Words technique is successful in improving the students' vocabulary in SDN 03 Mojo, Andong, Boyolali.